Efeitos de um protocolo de intervenção cinesioterapêutica com exergame nos parâmetros hemoodinâmicos de mulheres idosas sedentárias com hipertensão : ensaio clínico controlado randomizado - Perez, Fabrízzio Martin Pelle (2025)
Human aging is a natural and irreversible process, typically accompanied by various physiological changes. Alterations in the neuromuscular and cardiovascular systems are among those with the greatest negative impact on the elderly population. Among the most common age-related diseases are NonCommunicable Chronic Diseases (NCDs), with Systemic Arterial Hypertension (SAH) standing out. SAH is considered a major risk factor for the occurrence of cardiac events. Non-pharmacological treatments can contribute to the management and improvement of SAH. Among these, aerobic and resistance physical exercises are particularly noteworthy, and can be performed through virtual games, known as exergames. However, few studies have investigated the effects of exergames in older adults with SAH. In light of this, the general objective of this thesis was to evaluate and compare the effects of a kinesiotherapy intervention protocol using exergames on physiological parameters in sedentary older women with systemic arterial hypertension. The specific objectives were: (i) to assess upper and lower limb muscle strength at baseline, after 12 sessions, and post-intervention; (ii) to evaluate balance response at baseline, after 12 sessions, and post-intervention; and (iii) to assess the participants’ experience in interacting with the exergame. Methodologically, two scientific productions were developed. Scientific Production I aimed to identify gaps in existing evaluation practices and propose recommendations for future research, contributing to the development of more effective and engaging exergames and evaluation approaches. A scoping review was conducted to analyze user experience assessment methods and metrics in exergames across multiple databases, including ACM, IEEE, ScienceDirect, Springer, and PubMed, considering publications up to November 2023. The results indicate a preference for validated questionnaires, underscoring a commitment to methodological rigor and allowing for comparability. The conclusions highlight the need for more longitudinal and cross-cultural studies to enhance the understanding and improvement of user experience (UX) in exergames. Scientific Production II aimed to evaluate the effects of a kinesiotherapy intervention protocol using exergames on hemodynamic parameters (blood pressure and heart rate) in sedentary older women with SAH. This was a randomized controlled clinical trial involving 17 participants aged 60 years or older. The participants were stratified into an Intervention Group (IG) and a Control Group (CG). The IG underwent the kinesiotherapy intervention protocol using an exergame (Fisio Virtual), while the CG underwent a conventional kinesiotherapy protocol without the use of exergames. Sessions were held twice a week, each lasting 75 minutes, over a period of 12 weeks, totaling 24 sessions. Blood pressure and heart rate were monitored throughout the protocol using a multiparameter device. Balance was assessed using the Timed Up and Go test, and muscle strength was measured using an analog dynamometer. Muscle strength and balance assessments were conducted at three time points: pre-intervention, after six weeks, and after twelve weeks. Participants' experience with the exergame was also evaluated using the Game Experience Questionnaire – Post Game and open-ended questions. All assessments were conducted individually. Data were analyzed using the Statistical Package for Social Sciences® (SPSS®) version 30.0 for Windows®, with a significance level set at 0.05. After 12 weeks, no significant differences were found in hemodynamic parameters or physical fitness between the two groups. A reduction in systolic blood pressure, an increase in upper limb muscle strength, and a reduction in balance time were observed only in the control group compared to the exergame group. The kinesiotherapy protocol using exergames demonstrated a positive experience from the participants’ perspective. It can be concluded that a kinesiotherapy intervention protocol, whether conducted conventionally or through exergames, yielded similar effects and was positively experienced by participants in the intervention group.